2022
DOI: 10.1186/s12891-022-05376-9
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre validation study of a smartphone application to screen hand arthritis

Abstract: Background Arthritis is a common condition, and the prompt and accurate assessment of hand arthritis in primary care is an area of unmet clinical need. We have previously developed and tested a screening tool combining machine-learning algorithms, to help primary care physicians assess patients presenting with arthritis affecting the hands. The aim of this study was to assess the validity of the screening tool among a number of different Rheumatologists. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It is likely that once a diagnosis is made, treatment is normally initiated as a matter of urgency. These upstream changes may include the implementation of standardized referral patient-completed questionnaires to support referral decisions, 18,19 adoption of information technology 20 to electronically streamline care, 21 and increased involvement of extended health care professionals. [22][23][24] Identifying people with, for example, OA, might allow them to be directed to other health care professionals, such as physical or occupational therapists, removing them from the rheumatologist referral list.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that once a diagnosis is made, treatment is normally initiated as a matter of urgency. These upstream changes may include the implementation of standardized referral patient-completed questionnaires to support referral decisions, 18,19 adoption of information technology 20 to electronically streamline care, 21 and increased involvement of extended health care professionals. [22][23][24] Identifying people with, for example, OA, might allow them to be directed to other health care professionals, such as physical or occupational therapists, removing them from the rheumatologist referral list.…”
Section: Discussionmentioning
confidence: 99%
“…Each patient uploaded photos of their hands to the application and answered a 9-point questionnaire. The accuracy, precision, recall, and specificity in diagnosing RA were 85.1, 80.0, 88.1, and 82.7%, respectively [ 203 ]. This case is an example of the application of artificial intelligence in medicine.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] We need rapid identification or assessment of conditions in order not to delay treatment. Much rheumatologic research has been shown to be promising in radiographs, 11 magnetic resonance imaging, 12 and even musculoskeletal ultrasound. 13,14 All the above may be useful for countries that don't have enough imaging subspecialists.…”
Section: A S a Clini Cianmentioning
confidence: 99%